Opportunities and Challenges Facing the Profession of Translator in Africa (Global Journal of Human-Social Science, 2023)
In many African countries for historical reasons European languages including English French Spanish and Portuguese are used in schools churches public and private institutions Therefore translation from and into these languages is frequently done during international conferences as well as for international organisations and projects located in the African region The purpose of this paper is to discuss the opportunities and challenges of this linguistic situation for translators across Africa So far translation has played a major role in the progress of humanity and should continue to do so especially in Africa a continent that heavily depends on the wealth of knowledge and information available especially in English and in a few other languages History reveals that medicine which was originally practiced by the Arabs was introduced through translation into Western universities in the 8th century Nowadays thanks to the globalisation process translations are increasingly done by multinationals into many languages even in Africa
Keywords: freelance translator; translation technology; market demands; africa; professional ethics